Implementasi Terkait Keberhasilan Pembangunan Apartment Grha Aparna dalam Konteks Public Service Kepada Penghuni Apartemen Grha Aparna. - Rawung, Yemima Marchely; Muljanto, Muhammad Agus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Limited land, especially in big cities such as DKI Jakarta and Surabaya, as well as other areas, has caused land prices to skyrocket in all areas, making housing types such as apartments and condominiums the preferred choice for market consumers. In addition, the apartment's strategic location makes it the right choice in terms of price compared to very expensive condos in big cities. In addition, the increase in apartment sales or what is known as apartments has led to many fraudulent practices carried out by real estate developers or developers, so that consumers suffer huge losses due to this phenomenon. A particular problem is the commercialization of residential construction projects that have not yet been implemented but have been publicly marketed. This research was conducted and addressed to the Grha Aparna Apartment Development with the hope that researchers can find study material, namely the community's perspective regarding environmental and societal conditions in the Grha Aparna Apartment development area, besides that the research method that will be used in discussing this study is a descriptive qualitative research method and Literature study of journals or books that will be referred to in the process of studying this problem Keywords: Limited Land, Implementation, Apartments.